Association of serum water-soluble vitamin exposures with the risk of metabolic syndrome: results from NHANES 2003-2006 - Pei, Xun; Yao, Junjie; Ran, Simiao; Lu, Haifei; Yang, Shuo; Zhang, Yini; Wang, Miyuan; Shi, Heyuan; Tan, Aihua (Frontiers in Endocrinology, 2023)
Existing evidence has shown the associations between some vitamins and metabolic syndrome (MetS), but few epidemiological studies focused on the effects of multivitamin co-exposure on MetS. This study aimed to investigate the associations of individual and multiple water-soluble vitamins (i.e., vitamin C (VC), vitamin B9 (VB9) and vitamin B12 (VB12)) co-exposure with MetS, as well as the dose-response relationships among them. A cross-sectional study was conducted by employing the National Health and Examination Surveys (NHANESs) 2003-2006. Multivariate-adjusted logistic regression models were used to explore the relationships of individual serum water-soluble vitamins with MetS risk, and that of its components, including waist circumference, triglyceride, high-density lipoprotein, blood pressure and fasting plasma glucose. Restricted cubic splines were performed to explore the dose-response relationships among them. The quantile g-computation method was adopted to explore the associations of multiple water-soluble vitamins co-exposure with MetS risk and MetS components. This study totally involved 8983 participants, and 1443 were diagnosed with MetS. The MetS groups possessed higher proportions of participants aged ≥60 years, with BMI ≥30 kg/m2 and with insufficient physical activity. Compared with the lowest quartile, the third (OR=0.67, 95%CI: 0.48, 0.94) and highest quartiles (OR=0.52, 95%CI: 0.35, 0.76) of VC were associated with lower MetS risk. Restricted cubic splines showed negative dose-response relationships among VC, VB9 and VB12 and MetS. As for MetS component, higher VC quartiles were associated with lower waist circumference, triglyceride, blood pressure and fasting plasma glucose, and higher VC and VB9 quartiles were associated with higher high-density lipoprotein. VC, VB9 and VB12 co-exposure was significantly and inversely associated with MetS, with ORs (95% CI) of 0.81 (0.74, 0.89) and 0.84 (0.78, 0.90) in the conditional and marginal structural models, respectively. Besides, we found inverse associations of VC, VB9 and VB12 co-exposure with waist circumference and blood pressure, and a positive association between VC, VB9 and VB12 co-exposure and high-density lipoprotein. This study revealed negative associations of VC, VB9 and VB12 with MetS, and high water-soluble vitamin co-exposure was associated with low MetS risk.